ANALISIS STRATA NORMA PUISI AKU KARYA CHAIRIL ANWAR - Kurniasih, Titin Salma; Wijayanti, Tri Lutmasari (Jurnal Komposisi, 2022)
This study aims to analyze the strata of norms in the poem Aku Chairil Anwar. This research was conducted through a qualitative approach. The data taken comes from manuscripts, interviews, field notes, personal documents, memos and other official documents. Data collection was carried out by reading the contents of the poem repeatedly and then recording, identifying and classifying. The results of this study are the layers of sound found in the poem Aku by Chairil Anwar using a variety of cacophony sounds. In addition, the existence of an object layer in the poem Aku by Chairil Anwar which is stated is the actor, namely himself.